Social State-Legal State - Mirkamil Atavullaev (Scientific Trends, 2025)
This article examines the impact of social reforms carried out in recent years in New Uzbekistan on the foundations and mechanisms of public administration.
Keywords: New Uzbekistan, welfare state, mechanism, society, reform, constitution, law, legislation, corruption, rule of law.